Code of Professional Ethics of Public Accountants and Auditor Perfomance - I Gusti Ayu Asri Pramesti (Universitas Katolik Darma Cendika, 2025)
This study aims to examine the influence of the Five Principles of the code of professional ethics of Public Accountants on the performance of auditors. The study was conducted at the public accounting firm (KAP) in Bali Province. The sampling method used is purposive sampling, which produces a sample of 78 auditors from 14 KAP. This study used primary data collected through the dissemination of questionnaires. The data analysis technique used is multiple linear regression analysis. The findings show that integrity, objectivity, competence and professional prudence, confidentiality, and professional conduct positively affect the performance of auditors at KAP in Bali